Perancangan Jaringan Di Kota Pekanbaru Dengan Metode Algoritma Monte Carlo (Studi Kasus: LTE Multi-RAT UMTS) - Siti Maryam; Linna Oktaviana Sari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Pekanbaru still has poor and unstable network technology obtained from survey results using G-NetTrack Lite Software in 12 Districts, so the needs of network service users are not yet fully covered. Therefore, a motode is needed to solve the problems occurred. By using telecommunications that has high speed and it can serve the needs of service users. Technology that is capable fulfill to these needs and has high speed is Long Term Evolution (LTE). LTE has data transfer speed up to 50 Mbps for uplinks and 100 Mbps for downlinks. In this research network design using Multi-RAT technology is performed, Multi-RAT is a technology that can access more than one network. A in one the Multi-RAT technology can improve signal quality and optimize the network while working simultaneously. Furthermore, to validate the success of users who can connect to the LTE network designed, a Monte Carlo algorithm simulation is needed. Monte Carlo algorithm simulation is a probabilistic simulation solution of a problem given based on a randomization process. In the simulation test, as a result 96.5% of users are connected to the network with 3.082.47 Mbps Throughput value obtained from the Monte Carlo algorithm simulation that was carried out in Pekanbaru. It can be concluded that the design of UMTS Multi-RAT LTE network can be done because the average value of users and throughput connected with a high percentage is obtained.Keywords: LTE, Multi-RAT, UMTS, Monte Carlo Algorithm Simulation